2021
DOI: 10.21037/jtd-20-3257
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of primary spontaneous pneumothorax following bullectomy with pleurodesis or pleurectomy: A retrospective analysis

Abstract: Background: Primary spontaneous pneumothorax is managed initially with observation and chest tube placement, followed by surgical intervention in select cases. With little currently published evidence, the role of surgical pleurodesis or pleurectomy to reduce primary spontaneous pneumothorax recurrence is unclear.This study compares the recurrence rates of primary spontaneous pneumothorax following bullectomy alone versus bullectomy with pleurodesis or pleurectomy. Methods: A retrospective review was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This study analyzed 77 cases of PoR and explained that the temporal patterns of recurrence might be predictive of SR. As we described in Figure 1 , 27.3% (21/77) of the cases of PoR occurred within 30 days after surgery. This result is similar to the findings of Brophy et al, which showed that 26.3% (10/38) of PoR occurred within 30 days after surgery [ 8 ]. Moreover, patients in the ER group showed a better prognosis in terms of developing recurrent pneumothorax down the road than those in the LR group, and the period between surgery and recurrence played a significant prognostic factor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study analyzed 77 cases of PoR and explained that the temporal patterns of recurrence might be predictive of SR. As we described in Figure 1 , 27.3% (21/77) of the cases of PoR occurred within 30 days after surgery. This result is similar to the findings of Brophy et al, which showed that 26.3% (10/38) of PoR occurred within 30 days after surgery [ 8 ]. Moreover, patients in the ER group showed a better prognosis in terms of developing recurrent pneumothorax down the road than those in the LR group, and the period between surgery and recurrence played a significant prognostic factor.…”
Section: Discussionsupporting
confidence: 92%
“…To date, there has not been a clear consensus on the definition of postoperative recurrence of PSP. Brophy et al described a “true” postoperative recurrence as an episode that occurs at least 15 days after surgery and classified repetitive pneumothorax within 15 days as a “prolonged air leak” [ 8 ]. Onuki et al defined recurrence as an episode occurring at least 30 days after surgery and thought that recurrent events within the first 30 days after surgery were part of the staple-healing process [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Woo and colleagues attempted in their study to suggest a new classification system for the postoperative recurrence of SP [ 4 ] and tried to identify risk factors that could be related to a second recurrence. Following other reports, authors concluded that a pneumothorax occurring within 30 days from surgery should not be considered a true recurrence but part of the healing process [ 4 , 28 , 29 ]. They demonstrated that patients with postoperative recurrence within 30 days showed a better prognosis than patients with late recurrent episodes.…”
mentioning
confidence: 97%